A Case of Congenital Cystic Adenomatoid Malformation in a 10 Years Old Boy (Faridpur Medical College Journal, 2013)
Congenital Cystic Adenomatoid Malformation (CCAM) is a relatively rare congenital pulmonary cystic disease. By ultrasonography prenatal diagnosis can be made and most baby born without complication. Some babies need surgery at the first year of life for recurrent respiratory tract infection. Here a case of CCAM in a 10 year old boy is reported who presented with recurrent respiratory tract infection and underwent surgical resection successfully. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16900 Faridpur Med. Coll. J. 2013;8(1): 46-47